Physical Conditions of Fast Glacier Flow: 1. Measurements From Boreholes Drilled to the Bed of Store Glacier, West Greenland. Issue 2 (24th February 2018) - Doyle, S. H.; Hubbard, B.; Christoffersen, P.; Young, T. J.; Hofstede, C.; Bougamont, M.; Box, J. E.; Hubbard, A.
Abstract : Marine‐terminating outlet glaciers of the Greenland Ice Sheet make significant contributions to global sea level rise, yet the conditions that facilitate their fast flow remain poorly constrained owing to a paucity of data. We drilled and instrumented seven boreholes on Store Glacier, Greenland, to monitor subglacial water pressure, temperature, electrical conductivity, and turbidity along with englacial ice temperature and deformation. These observations were supplemented by surface velocity and meteorological measurements to gain insight into the conditions and mechanisms of fast glacier flow. Located 30 km from the calving front, each borehole drained rapidly on attaining ∼600 m depth indicating a direct connection with an active subglacial hydrological system. Persistently high subglacial water pressures indicate low effective pressure (180–280 kPa), with small‐amplitude variations correlated with notable peaks in surface velocity driven by the diurnal melt cycle and longer periods of melt and rainfall. The englacial deformation profile determined from borehole tilt measurements indicates that 63–71% of total ice motion occurred at the bed, with the remaining 29–37% predominantly attributed to enhanced deformation in the lowermost 50–100 m of the ice column. We interpret this lowermost 100 m to be formed of warmer, pre‐Holocene ice overlying a thin (0–8 m) layer of temperate basal ice. Our observations are consistent with a spatially extensive and persistently inefficient subglacial drainage system that we hypothesize comprises drainage both at the ice‐sediment interface and through subglacial sediments. This configuration has similarities to that interpreted beneath dynamically analogous Antarctic ice streams, Alaskan tidewater glaciers, and glaciers in surge. Plain Language Summary: Greenland's fast flowing tidewater glaciers account for significant contributions to sea level rise, yet little is known about the conditions within and beneath them. We instrumented boreholes drilled to the bed of Store Glacier with sensors to measure ice temperature and deformation, and subglacial water properties. These data reveal that the fast flow of Store Glacier is mainly caused by motion at the ice bed interface driven by highly pressurized subglacial water and basal sediments, together with a significant component of ice deformation concentrated in the lowermost 80 m of ice deposited in the last glacial period. The subglacial conditions, including inefficient subglacial drainage at high pressure, are similar to those observed beneath fast‐flowing Antarctic ice streams, Alaskan tidewater glacier, and glaciers in surge. Key Points: Borehole sensors provide insight into the basal conditions and thermal structure of Store Glacier Fast basal motion is facilitated by inefficient subglacial drainage at high pressure and a soft bed Temperate basal ice is thin or absent and ice deformation is enhanced within pre‐Holocene ice